2010 35th IEEE Photovoltaic Specialists Conference 2010
DOI: 10.1109/pvsc.2010.5616526
|View full text |Cite
|
Sign up to set email alerts
|

Carrier transport properties of flash-lamp-crystallized poly-Si films

Abstract: We have investigated carrier transport properties of µm-order-thick polycrystalline silicon (poly-Si) films formed by flash lamp annealing (FLA) of precursor amorphous Si (a-Si) films on glass substrates. The Hall mobility of flashlamp-crystallized (FLC) poly-Si films decreases as doping concentration increases, and then reversely increase with further increase in doping concentration, both in the cases of p-and n-type poly-Si films. The tendency observed is characteristic of poly-Si materials having a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…We have found that these remaining H atoms can be utilized for the termination of Si dangling bonds by furnace annealing, 14) and the defect density can be decreased to $5 Â 10 16 cm À3 . 15) This value is close to those of CVD a-Si and microcrystalline Si films, and further reduction of defect density will hopefully be realized by optimizing the defectterminating annealing conditions and/or applying other passivation techniques.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…We have found that these remaining H atoms can be utilized for the termination of Si dangling bonds by furnace annealing, 14) and the defect density can be decreased to $5 Â 10 16 cm À3 . 15) This value is close to those of CVD a-Si and microcrystalline Si films, and further reduction of defect density will hopefully be realized by optimizing the defectterminating annealing conditions and/or applying other passivation techniques.…”
Section: Resultssupporting
confidence: 63%
“…Relatively high Hall mobilities of $10 cm 2 V À1 s À1 have actually been observed in the FLC poly-Si films. 13) Effective carrier collection can be expected in solar cells fabricated using FLC poly-Si films. On the other hand, the passivation of grain boundaries would be one of the most important issues in realizing high-efficiency solar cells using FLC poly-Si films, because of the absence of a-Si tissue passivating grain boundaries, unlike CVD microcrystalline Si films.…”
Section: Resultsmentioning
confidence: 99%
“…Another likely reason for the difference is large difference in poly-Si film thickness: 50 nm for excimer-laser-crystallized poly-Si films The defect density obtained in this study is much lower than that of FLC poly-Si films formed from hydrogenated Cat-CVD a-Si films, i.e., $5 Â 10 16 /cm 3 , after furnace annealing under N 2 atmosphere. 20) This might also be due to the difference in grain size. We have succeeded in obtaining 3-m-thick poly-Si films with a low defect density equivalent to that of device-grade CVD a-Si and/or microcrystalline Si (c-Si) films.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the presence of dispersed material structure requires the use of certain techniques and methods, that would bring characteristics of polycrystalline silicon in SOI structures closer to those of monocrystalline, for which high values of charge carriers mobility are inhered. In particular, the authors of [17] have made the flash-lamp-crystallized p-and n-type poly-Si films, in which the Hall mobility was decreasing with the increase of the doping concentration and then reversely rising with the further increase of the latter. Among the other known methods for reducing the structural defects, laser recrystallization [18] of initial poly-Si makes it possible to substantially increase the charge carrier mobility in a layer.…”
mentioning
confidence: 99%